2021
DOI: 10.15446/ing.investig.93803
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Personality Evaluation from Transliterations of YouTube Vlogs Using Classical and State of the art Word Embeddings

Abstract: The study of automatic personality recognition has gained attention in the last decade thanks to a variety of applications that derive from this field. The big five model (also known as OCEAN) constitutes a well-known method to label different personality traits. This work considers transliterations of video recordings collected from YouTube (originally provided by the Idiap research institute) and automatically generated scores for the five personality traits which also were provided in the database. The tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
2
1
Order By: Relevance
“…While for Youtube dataset, this research achieves an average f1 score 0,741. Compared to previous results that used Youtube dataset also, this result provided a good result and was better than the research done by [15] that resulted best f1 score 0,612. One of the reasons for the result is this research modified the dataset to minimize imbalance class with the data augmentation method.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…While for Youtube dataset, this research achieves an average f1 score 0,741. Compared to previous results that used Youtube dataset also, this result provided a good result and was better than the research done by [15] that resulted best f1 score 0,612. One of the reasons for the result is this research modified the dataset to minimize imbalance class with the data augmentation method.…”
Section: Discussioncontrasting
confidence: 55%
“…Decision tree and SVM algorithm were used and produced better results over baseline average performance. Another research using Youtube dataset was also conducted by [15]. This research uses Youtube translations only to create a model using Word2Vec, GloVe, and BERT as feature extraction methods then uses SVM and SVR for classification.…”
Section: Related Workmentioning
confidence: 99%
“…Jiang, et al [8] presented a novel approach to automatic personality detection using RoBERT and attentive neural networks for the Big Five. Furthermore, Padon et al [9] adopted three pre-trained language models -Word2Vec, GloVe, and BERT to classify Big Five personality traits. Demerdash et al [10] used three pre-trained models including Elmo, ULMFiT, and BERT to extract features and achieved the State-of-the-Art results on myPersonality dataset.…”
Section: Text-based Big Five Personality Predictionmentioning
confidence: 99%
“…The work of Roussmann et al [6] confirms that personality is related to the situations people encounter and their interpretations of them, so it is possible to predict how they will act in their daily lives through the OCEAN personality model. Lopez et al [7], who attempted to automate personality assessments from transliterations of YouTube vlogs using classic and state-of-the-art word embeddings, argue that personality trait studies based on language patterns also need to take into account the knowledge of psychologists and psycholinguists to collect and label data. Holman et al [8] researched the interaction between the Big-5 personality traits and work characteristics, and it was found that the work characteristics had an impact on the personality traits.…”
Section: Introductionmentioning
confidence: 99%